Measuring Community Strength and Social Capital - Robert Stimson; John Western; Scott Baum; Yolanda Van Gellecum (European Regional Science Association (ERSA), 2003)
In 2001/02 five case study communities in both metropolitan and regional urban locations in Australia were chosen as test sites to develop measures of community strength on four domains: natural capital; produced economic capital; human capital; and social and institutional capital. Secondary data sources were used to develop measures on the first three domains. For the fourth domain'social and institutional capital?primary data collection was undertaken through sample surveys of households. A structured approach was devised. This involved developing a survey instrument using scaled items relating to four elements: formal norms; informal norms; formal structures; and informal structures'which embrace the concepts of trust, reciprocity, bonds, bridges, links and networks in the interaction of individuals with their community inherent in the notion social capital. Exploratory principal components analysis was used to identify factors that measure those aspects of social and institutional capital, with confirmatory analysis conducted using Cronbach's Alpha. This enabled the construction of four primary scales and 15 sub-scales as a tool for measuring social and institutional capital. Further analyses reveals that two measures'anomie and perceived quality of life and wellbeing?relate to certain primary scales of social capital.
Keywords: 330